Teaching of the Basic Money and Financial Institutions Course - Kaufman, George G. (Journal of Financial and Quantitative Analysis, 1976)
Like any course, the basic money and financial institutions course, or money and banking as it is more frequently designated, takes on the unique coloration of the instructor. However, this course appears to be so affected more than most other finance and economics courses at this level. This occurs because, although it is a second course, it is still a very broad course in design, and more importantly, because it encompasses the three approaches to the teaching of economics and finance–description, theory, and policy. Different instructors emphasize different aspects, at times, to the almost total exclusion of one or both of the other two. But, judging from the financial failure of textbooks that have attempted to focus on just one of these aspects, say, financial institutions or monetary economics, it appears that most instructors prefer the broader and more diffuse coverage. And so do I.